Rancang Bangun Alat Uji Balancing Universal Menggunakan Metode Vdi 2222 - M. Ferdiman Setepu; Musthafa Akbar; Feblil Huda (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The machines with rotating shaft on the highest level of rotation which is until 3000 rpm like turbine will be dangerous if there’s an unbalance occur while working out. The low unbalance mass with high rotation shall also cause so high centrifugal force that the bearing would be broken easily. It severely damages all systems. Universal balancing testing machine is one of the alternatives used to detect the machine damages with various dimensions. It also can detect some other broken components by measuring the vibration without any physical contact to the machines. The universal balancing testing machine design uses VDI 2222 method by deciding product concept from various ones which are created then developed into a product. From this design, it gives a static analysis result from analytic and finite element methods. The results are the shaft diameter sized 15.12 mm, and the value of stress analysis for base bearing for maximum voltage is 6.6 MPa. It could be classified into the safe one as the voltage is smaller than material license which is in the amount of 180 MPa with safety factor in 27.Keywords: unbalance, VDI 2222, Analytic method, Finite Element Method